ANALISIS PENGARUH NILAI PRODUKSI, NILAI INVESTASI, NILAI UPAH TERHADAP PENYERAPAN TENAGA KERJA PADA INDUSTRI BAJU TIDUR BATIK BAGAN - Giman, Febrina Sari; Mardiana, Mardiana; Utami, Bunga Chintia (Jurnal Manajemen dan Bisnis, 2023)
This study aims to determine the influence that production value, investment value, and pay value have on employment in the industrial sector of batik Bagan weaving in the Bangko subdistrict of the Rokan Hilir regency. For the sake of this study's sample, the overall population was broken up into 24 different business units, called nightgown bagan. Several linear methods were used to the analysis of the data that was used in the cross-sectional study. The results of this study indicate that the value of production, the value of investment, and the value of remuneration all have a significant and beneficial impact on employment in the batik Bagan nightgown industry in the Bangko District of the Rokan Hilir regency. The findings of the regression analysis produced an Adjusted R2 value of 0.798, which indicated a 79.8% influence of production value, investment value, and minimum wage value on employment in the batik nightgown industry in the District Bangko Rokan Hilir regency. In addition, another 20.2% of the industry's employment is influenced by other variables that were not investigated in the study. The outcomes of the research indicate that the investment value, production value, and minimum wage all have a positive influence on employment levels in the District Bangko Rokan Hilir batik textile industry.Keywords: (bahasa inggris; 3-5 keywords) Investmet, wage, production value, labor